Opioid Misuse Among HIV-Positive Adults in Medical Care: Results From the Medical Monitoring Project, 2009–2014. (1st February 2019) - Lemons, Ansley; DeGroote, Nicholas; Peréz, Alejandro; Craw, Jason; Nyaku, Margaret; Broz, Dita; Mattson, Christine L.; Beer, Linda
Abstract : Background: People living with HIV are prescribed opioids more often and at higher doses than people who do not have HIV, and disproportionately experience risk factors for substance use disorder, which suggests they could be at increased risk of the misuse of opioids. Researchers also suggest that opioid misuse negatively affects various HIV clinical outcomes, increasing the risk of transmission to partners with an HIV-negative status. Methods: We calculated weighted percentages and 95% confidence intervals to estimate substance use characteristics among a probability sample of 28, 162 HIV-positive adults receiving medical care in the United States who misused opioids (n = 975). Then, we used Rao-Scott χ 2 tests to assess bivariate associations between opioid misuse and selected characteristics. Results: In all, 3.3% misused opioids. Misuse was more common among young adults, males, and non-Hispanic whites. Persons who misused opioids were less likely to: have been prescribed antiretroviral therapy (ART) (88.7%), report being adherent to ART medications in the past 3 days (78.1%), and have durable viral suppression (54.3%) than persons who did not misuse opioids (92.5%, 87.7%, and 64.7%, respectively). Persons who misused opioids were more likely to report condomless sex with partners of negative or unknown HIV status while not durably virally suppressed (11.7% vs 3.4%) than persons who did not misuse opioids. Conclusions: Opioid misuse among adults receiving HIV medical care is associated with inadequate ART adherence, insufficient durable viral suppression, and higher risk of HIV transmission to sexual partners.